The Impact of Perceived Supervisor Support on OCB: The Moderating Effect of Introversion - Naheed Sultana; Osaid Rabie; Mariam Farooq; Ayesha Amjad (The Lahore Journal of Business)
This study examines the extent to which introversion moderates the relationship between perceived supervisor support and organizational citizenship behavior (OCB). Based on a sample of 586 employees working in Pakistan’s education sector, we find that introverts have a positive moderating effect on the indirect relationship between perceived supervisor support, work engagement and OCB. This suggests that supervisor support fosters work engagement and, in turn, OCB.